A study of the effects of minor additives to Pb-Bi eutectic: Designing novel Pb-Bi-X liquid alloys for heat transfer applications. (5th December 2018) - Popović, M.P.; Olmsted, D.L.; Bolind, A.M.; Asta, M.; Sohn, S.; Schroers, J.; Shao, R.; Hosemann, P.
Abstract: Lead-bismuth eutectic (LBE) is a promising heat transfer fluid candidate for fast-neutron nuclear reactors and for concentrating solar power systems, due to its low melting point and advantageous thermophysical properties, but suffers from causing liquid-metal corrosion in many solids used as structural materials. Adding a suitable element to LBE to form a ternary alloy, along with proper oxygen concentration in LBE at desired temperature, might provide a formation of the protective intermetallic layers besides the formation of protective oxides on the solid surface. In this study, novel Pb-Bi-X alloys, as improvement LBE, have been designed for a broad temperature range, with X additions selected based on thermodynamic considerations and modeling, and experimentally evaluated at 700 °C. Thermodynamic calculations indicated Pb-Bi-Sb and Pb-Bi-Ge as the best candidates, and experiments provided some evidence of possible intermetallic formation of Sb with Fe-Cr-Al alloy constituents. The work pointed to the need for further research into the compatibility with structural materials at high temperatures. Graphical abstract: Only four of the studied candidate additives (Y, Sb, Co and Ge) have the oxygen concentration limit for oxidation of additive at 250 °C above the O concentration limit of alumina formation at 800 °C, i.e. the oxygen window existing (left). Among these four, Ge and Sb have proven to be the best candidates, based on the criteria of possibility of intermetallic formation in the scales along with the oxide formation. The evidence of possible intermetallic formation of Sb with Fe-Cr-Al alloy constituents in the scale formed on solid surface (in the liquid-solid interface) was obtained by the EDS line-scan (right). This supports the idea of enhanced corrosion protection of Cr-Al-steels by the intermetallic passivation along with the oxidative one. Highlights: Thermodynamic calculations found 4 elements solvable in liquid Pb-Bi alloy & creating intermetallic phases on Fe-Cr-Al steel. Sb and Ge were the best additives to promote both intermetallic and alumina scales as protection against corrosion. Corrosion tests of Fe-Cr-Al steel in liquid Pb-Bi-Sb alloy indicated the formation of Sb intermetallic phase besides Al2 O3 .